2010
DOI: 10.1002/cctc.201000021
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium Polyoxometalate: An Ionic Liquid Catalyst for Esterification and Oxidative Esterification

Abstract: A new family of polyoxometalate‐based ionic liquids (POM‐IL) is synthesized, characterized, and employed as catalysts in the esterification of various alcohols with acetic acid. The ionic liquid catalyst shows high activity and gives excellent yields of esters. An emulsion forms between the IL catalyst and substrates during the reaction and promotes the catalytic process. After reaction, the emulsion can conveniently be broken by the addition of a weakly polar organic solvent to facilitate the separation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…The heterogeneous behavior may originate from the alkylammonium cation that provides the rigidity of the crystal structure in the POM salt, hindering the dissolution of the peroxo vanadium paired intermediate [C 3 CNtma] 4 [H 3 PMo(V 5+ )] 4À . 39,40 On the other hand, the classical heterogeneous supported POM catalyst PMoV 2 /SiO 2 only shows a remarkably lower activity than [C 3 CNpy] 4 HPMoV 2 with a low surface area 8.9 m 2 g À1 , though it has a high BET surface area 242 m 2 g À1 .…”
Section: Phase-transfer Reaction Mechanism Proposed For [C 3 Cnpy] 4 mentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneous behavior may originate from the alkylammonium cation that provides the rigidity of the crystal structure in the POM salt, hindering the dissolution of the peroxo vanadium paired intermediate [C 3 CNtma] 4 [H 3 PMo(V 5+ )] 4À . 39,40 On the other hand, the classical heterogeneous supported POM catalyst PMoV 2 /SiO 2 only shows a remarkably lower activity than [C 3 CNpy] 4 HPMoV 2 with a low surface area 8.9 m 2 g À1 , though it has a high BET surface area 242 m 2 g À1 .…”
Section: Phase-transfer Reaction Mechanism Proposed For [C 3 Cnpy] 4 mentioning
confidence: 99%
“…1 Great efforts have been made to achieve the catalytic phase-transfer system, such as esterification, 2 oxidative esterification, 3 carbonylation, 4 Stetter reaction, 5 etc. In particular, polyoxometalate (POM) hybrid-catalyzed H 2 O 2 -based organic oxidations have been revealed as the phase-transfer reactions for the oxidation of olefins 6,7 and alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…A careful literature survey shows that there are no reports on direct oxidative esterification of aldehydes over lacunary POMs. However, only two reports are available on this reaction with H 2 O 2 using acidic form of supported POMs (12-tungstophosphoric acid) (95,96). From Table 4 it was observed that the 30% PW 11 /ZrO 2 system was not surface type heterogeneous catalyst, in which the catalytic activity is directly proportional to surface area but it is a pseudo-liquid type in which catalytic activity is proportional to the total acidity.…”
Section: Oxidative Esterification Of Aldehydesmentioning
confidence: 92%
“…After reaction, the catalyst was found to be self-precipitating, which made the recovery and reuse of the catalyst very convenient. Wang et al [30] [31], and employed as catalyst for esterification of various alcohols with acetic acid. This IL catalyst showed high activity and excellent esters yields.…”
Section: Introductionmentioning
confidence: 99%